PENERAPAN SISTEM MANAJEMEN KINERJA, SISTEM PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN - Al, M (Universitas Muhammadiyah Magelang, 2010)
The relationship between Management performance system (SMK), management career system (SPK) to oorganizational comitment and performance has been attracting researcher?s attention. This study examine the relation between SMK-SPK in organization with comitment organizational to employee performance. This study with a population of bank employees in Magelang to sample as many 145 people, to test hypothesis using SEM. This result support The Use of SMK and SPK will increase employee performance and comitment organizational, but interaction between SPK-SMK with organizational comitment will reduce employee performance.